Prophylactic Role of Oral L-Arginine on Histological and Contractile Changes in a Rat Chronic Bladder Injury Model - ERCAN, FERİHA; TARCAN, TUFAN (KARGER, 2008)
Introduction: The effect of L-arginine on bladder tissue structure and function in a rat bladder injury model were investigated. Methods: 24 male Sprague-Dawley rats were used. The control group received a regular diet. The L-arginine group received oral L-arginine (1 g/day). The protamine sulfate (PS) group received intravesical PS every 48 h (0.5 ml, 5 mg/ml). L-Arginine was administered to the PS+L-arginine group in addition to PS. At the end of 1 week, bladder tissues were processed for histological and functional studies. Results: The PS group revealed urothelial damage with glycosaminoglycan layer irregularity and mast cell infiltration which was not evident in the PS+L-arginine group. 120 m M potassium and electrical field stimulation (EFS)-induced contractions in the PS group were significantly lower than in other groups, whereas carbachol-induced contractions were not significantly different. Relaxation responses of precon-tracted strips to EFS and isoproterenol did not reveal a significant decrease in the PS group, whereas L-arginine significantly enhanced these responses in PS-treated animals. Conclusions: Intravesical PS causes urothelial damage and inflammation that is associated with significant changes in rat bladder tissue contractility. Oral L-arginine treatment is found to prevent these histological and contractile alterations. Our findings may indicate the nitric oxide-cGMP pathway as a possible therapeutic target in various bladder diseases associated with urothelial damage. Copyright (c) 2008 S. Karger AG, Basel
Keywords: L-Arginine; Oral L-arginine, prophylactic role; Protamine sulfate; Bladder injury; Rat chronic bladder injury model; NITRIC-OXIDE SYNTHASE; LOWER URINARY-TRACT; INTERSTITIAL CYSTITIS; RESPONSES; BARRIER; NECK